Studi Bioinformatika Tanaman Genus Nigella terhadap Kanker Payudara Tipe Basal Berbasis Transkriptomik dan Farmakologi Jaringan - Saipul Maulana; Muhammad Sulaiman Zubair; Muhammad Azwar AR (Jurusan Farmasi Poltekkes kemenkes Makassar, 2026)
Basal-type breast cancer (Triple-Negative Breast Cancer, TNBC) is an aggressive subtype characterized by poor prognosis and limited conventional therapeutic options due to the absence of hormone receptor and HER2 expression. To address this challenge, this study aims to elucidate the molecular mechanisms of compounds derived from the Nigella genus against basal-type breast cancer using a Network Pharmacology approach integrated with transcriptomic data. This in silico experimental study began with the identification of 433 bioactive compounds from the Nigella genus retrieved from databases, which were predicted to target a total of 2,227 potential proteins. Transcriptomic analysis was performed using the GSE7904 dataset, comparing 18 basal-type breast cancer samples with 7 normal control samples. Statistical analysis identified 9,666 significantly Differentially Expressed Genes (DEGs). Venn diagram intersection analysis between the compound targets and DEGs revealed 996 overlapping genes, which were designated as potential candidate targets. Protein–Protein Interaction (PPI) network topology analysis identified EGFR (Epidermal Growth Factor Receptor) as the top hub protein with a degree value of 110, followed by SRC (108) and PIK3CA (70). Functional enrichment analysis (KEGG) validated EGFR as a critical receptor in TNBC, initiating oncogenic signaling pathways such as MAPK and PI3K–Akt that drive basal-type cancer cell proliferation. Bioactive compounds from Nigella were predicted to exert their effects by interacting with membrane receptors and inhibiting tyrosine kinase activity. Therapeutic intervention targeting EGFR using bioactive compounds from the Nigella genus therefore represents a promising strategy to overcome resistance and aggressiveness in basal-type breast cancer.